A Skills-Based Longitudinal Intervention for Clinician Educators: Addressing Implicit Bias in Patient Care and the Clinical Learning Environment - Hana Khidir; Savanna Carson; Stefanie Vassar; Arash Nafisi; Gezman Abdullahi; Sural Shah; Hrishikesh K. Belani; Benjamin P. L. Meza; Arleen F. Brown; Cristina M. Gonzalez (Journal of Continuing Education in the Health Professions, 2026)
Introduction: Implicit bias contributes to health care disparities. Addressing implicit bias is one focus of health professions education and learners desire instruction in the topic. Few faculties received skills-based instruction in addressing implicit bias during their own education and training and often feel ill-equipped to facilitate this instruction. Recognizing faculty are both learners and teachers in addressing implicit bias, the authors developed a longitudinal faculty development program informed by the implicit bias recognition and management (IBRM) framework. Methods: The program, IBRM for Faculty (IBRM4Fac), comprised 8 sixty-minute sessions delivered virtually from November 2020 to March 2021 at an academic safety-net health system. Program goals were skills development, including restoring rapport with patients, debriefing biased encounters, and addressing bias from patients. An external expert in IBRM led each session; materials included slides, worksheets to guide skills-development, and an audience response system. The mixed-methods program evaluation used preprogram/postprogram surveys. Results: Approximately 50 faculty primarily from the department of medicine were invited to participate in the program, N = 17 (34%) participated. Significant improvements occurred in 9/10 surveyed domains of IBRM ( P < .05). Narrative responses analyzed through reflexive thematic analysis yielded three themes: (1) Personal strategy development; (2) Personal obstacles to sustained organizational change; and (3) Systemic barriers to sustained organizational change. Discussion: IBRM4Fac enhanced faculty confidence in addressing implicit bias, and helped faculty overcome identified challenges to implement strategies for teaching, role-modeling, and systems change in addressing implicit bias. Despite a small sample, our program could inform faculty development in addressing implicit bias in clinical and teaching encounters.